Mekanisme Penindakan Terhadap Oknum Anggota Polisi yang Melakukan Pelanggaran Kode Etik Oleh Bidang Profesi Dan Pengamanan (PROPAM) - Dahri Iskandar (Albayan Journal of Islam and Muslim Societies, 2024)
The attitudes and behavior of members of the Indonesian National Police are governed by the Police Professional Code of Ethics as stipulated in Police Regulation Number 7 of 2022. This study examines the legal framework and enforcement mechanisms implemented by Propam against police officers who violate the code of ethics, as well as the challenges and efforts encountered in the process. The research is descriptive-analytical with an empirical juridical approach. Data were collected through literature review and field research at the North Sumatra Regional Police, consisting of both primary and secondary sources. The findings reveal that enforcement against ethical violations includes not only ethical sanctions but also criminal penalties under the Indonesian Criminal Code and administrative sanctions as regulated in Police Regulation No. 7 of 2022. The enforcement process begins with public reports, internal investigations, and hearings before the Police Code of Ethics Commission, which consists of three to five members, including the adjudicator (Ankum), prosecutor, and advisor, all from within the police institution. Challenges include the absence of alleged violators, lengthy trial proceedings, and limitations in internal supervision. This study emphasizes the importance of consistent enforcement by Propam to uphold professionalism and the integrity of the police institution.